Emerging adults’ financial responsibility and self-confidence as predictors of income - Burr, Emily A. (Kansas State University, 2013)
Many individuals in their teens and twenties believe achieving financial self-sufficiency is an important part of becoming an adult (Arnett, 2000); yet the research on this topic is very limited. The level of general responsibility a young adult obtains is related to their general level of self-confidence (e.g., Shim, Serido, Bosch & Tang, 2013). However, the relationship between financial responsibility and self-confidence is currently unknown. Additionally, the relationship between self-confidence and annual income among young adults is largely unknown. This is the first study to advance current knowledge with a large (N = 474) and longitudinal dataset of emerging adults. The goal of this study is to test the underlying process that may explain variation of annual income among emerging adults from the Transition to Adulthood Supplement, a subset of the Panel Study of Income Dynamics (PSID). The study used a structural equation model (SEM) to test three waves of data across four years. Results from the SEM analysis demonstrated that higher levels of financial responsibility were associated with higher levels of self-confidence two years later. Additionally, the findings showed that higher levels of self-confidence were associated with higher levels of annual income after an additional two years. The results suggest the importance of building financial responsibility and self-confidence in emerging young adults.
Keywords: Financial responsibility; Income; Self-confidence; Transition into adulthood; Emerging adults; Social Sciences Education (0534)